A new distinctively banded species of Panaqolus (Siluriformes: Loricariidae) from the western Amazon Basin in Peru - Lujan, Nathan K.; Steele, Sarah; Velasquez, Miquel (Zootaxa, 2013)
Panaqolus albivermis is described as a new species based on four specimens from the San Alejandro River, a tributary of the upper Ucayali River in central Peru. Panaqolus albivermis is diagnosed from all other Panaqolus except P. maccus by having head, body, and fins with widely separated small white to yellow spots, vermiculations, and/or thin oblique bands on a black base (vs. exclusively small white to yellow spots on a black base in P. albomaculatus, generally broad oblique bands of alternating light to dark brown in P. changae, P. gnomus, P. purusiensis, and a uniformly dark gray to black body color in P. dentex, P. koko, and P. nocturnus); P. albivermis can be diagnosed from P. maccus by having a black base color (vs. brown), by having parallel dentary tooth cups (vs. acute intermandibular tooth cup angle), and by having a larger known adult body size (95.8 mm SL vs. 84.8).